Where the Action Is—Leukocyte Recruitment in Atherosclerosis - Mauersberger, Carina; Hinterdobler, Julia; Schunkert, Heribert; Kessler, Thorsten; Sager, Hendrik B. (Frontiers in Cardiovascular Medicine, 2022)
Atherosclerosis is the leading cause of death worldwide and leukocyte recruitment is a key element of this phenomenon, thus allowing immune cells to enter the arterial wall. There, in concert with accumulating lipids, the invading leukocytes trigger a plethora of inflammatory responses which promote the influx of additional leukocytes and lead to the continued growth of atherosclerotic plaques. The recruitment process follows a precise scheme of tethering, rolling, firm arrest, crawling and transmigration and involves multiple cellular and subcellular players. This review aims to provide a comprehensive up-to-date insight into the process of leukocyte recruitment relevant to atherosclerosis, each from the perspective of endothelial cells, monocytes and macrophages, neutrophils, T lymphocytes and platelets. In addition, therapeutic options targeting leukocyte recruitment into atherosclerotic lesions—or potentially arising from the growing body of insights into its precise mechanisms—are highlighted.